2016
DOI: 10.1063/1.4961688
|View full text |Cite
|
Sign up to set email alerts
|

Roles of bulk viscosity on Rayleigh-Taylor instability: Non-equilibrium thermodynamics due to spatio-temporal pressure fronts

Abstract: Direct numerical simulations of Rayleigh-Taylor instability (RTI) between two air masses with a temperature difference of 70 K is presented using compressible Navier-Stokes formulation in a non-equilibrium thermodynamic framework. The two-dimensional flow is studied in an isolated box with non-periodic walls in both vertical and horizontal directions. The non-conducting interface separating the two air masses is impulsively removed at t = 0 (depicting a heaviside function). No external perturbation has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The term given by, ω ∇ • V , is due to compressibility, and RTI should justifiably depend upon bulk viscosity as noted from the constitutive relation between stress and rates of strain tensors. Equation (1) demonstrates the need for predicting RTI using the compressible flow formulation along with the bulk viscosity contribution, as has been reported in [12,14], and the same formulation is also used here. Thus, without using the Stokes' hypothesis, the linear regression model for the bulk viscosity based on acoustic dispersion and attenuation experimental data of Ash et al [15] is utilized here also.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The term given by, ω ∇ • V , is due to compressibility, and RTI should justifiably depend upon bulk viscosity as noted from the constitutive relation between stress and rates of strain tensors. Equation (1) demonstrates the need for predicting RTI using the compressible flow formulation along with the bulk viscosity contribution, as has been reported in [12,14], and the same formulation is also used here. Thus, without using the Stokes' hypothesis, the linear regression model for the bulk viscosity based on acoustic dispersion and attenuation experimental data of Ash et al [15] is utilized here also.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, the box is considered to be thermally insulated, which enables it to be viewed as an universe, without any mass, momentum, and energy transfer with the outside. The ensuing RTI upon removal of the partition enables one to view the process as one of non-equilibrium thermodynamics, as reported for a two-dimensional (2D) flow in [14,20,21] and a three-dimensional (3D) flow with A t = 0.2, due to initial temperature differential of 149K. In Read's experiments [22], two geometrical setups were considered with the purpose of providing results for 2D and 3D flows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no such publication. However, we did report the data that were employed in Figure 7 of that article, 5 as part of a NASA contractor report, 1 and that may explain the error. This author believes that Sengupta et al have identified an important non-equilibrium effect, but they should have been more thorough in reviewing the underlying non-equilibrium physics literature.…”
mentioning
confidence: 99%